Efficient coded excitation beamforming system for medical ultrasound imaging - Cao, Ji (2011)
Conventional ultrasound medical imaging systems use simple high voltage pulses of around 200V peak to drive the ultrasound transducer to emit short ultrasonic pulses and multiple multi-bit analog to digital converters (ADC) to digitize the return echo signals, thus making it extremely challenging to integrate the transmit and receive electronic circuits onto a single chip. With coded excitation techniques, the necessary drive voltage can be reduced if the duration of the drive signal (coded signal in this case) is increased. Pulse compression techniques are used to compress the returned signal to achieve the high resolution needed for imaging. Oversampling sigma delta ADCs have much smaller silicon area compared to the equivalent multi-bit ADCs. The motivation of the project is to realize an efficient front-end transmit and receive system for medical ultrasound imaging, which takes advantage of the low drive voltage of the coded excitation method and the hardware efficiency of the sigma delta ADC, for possible single-chip implementation.